Analysis of Factors Related to Community's Interest in Saving on Waste Bank in The City of Banda Aceh - Nasrol Nasrol; Aulina Adamy; Irwan Saputra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2020)
Developed countries have used various strategies to address issues related to awareness, technology, socio-economics, and governance in waste management. The proposed solution is a community waste buyback program. In short, a repurchase program is a mechanism to collect something from users in exchange for money, but unfortunately there are still very few people who are interested in this program. This study used a cross sectional design for the community in 12 gampoeng in Banda Aceh City from 10 February to 10 April 2021 . Sampling was done by proportional random sampling method to 99 respondents . The data collected is  public awareness, knowledge, experience, training, age, education, occupation and income . Data was collected using a questionnaire which was distributed directly with the help of 6 enumerators . Data analysis was carried out in multi-variety using logistic regression analysis at a 95% confidence level . The results of univariate analysis show that 74.75% are aged 20-35 years, 73.74% are educated in the middle category, 73.74% are unemployed, 75.76% have low income categories, 57.58% of respondents have low interest in saving. In the waste bank, 55.56% of respondents have a low level of awareness, 57.58% have low knowledge, 64.65% have no experience, and 62.63% have never attended training . The results of the bivariate analysis showed that there was a significant relationship between income ( p = 0.008), awareness ( p = 0.001), knowledge ( p = 0.001), training ( p = 0.003) and there was no relationship between age, education, occupation and experience with interest in saving. in the waste bank ( p  0.05). The final conclusion of this study shows that income is the factor most related to people's interest in saving at a waste bank in Banda Aceh city with OR=9.0 (95% CI: 2.372-40.8) with p = 0.002. It is necessary to increase knowledge through structured education by adjusting the schedule to the community in a sustainable manner